Jejuno-Ileal tumors: a retrospective study - Thakur, Mohim; Vats, Ravinder; Goel, Deep; Bhalla, Virandera P. (International Surgery Journal, 2021)
Background: Primary tumors of the jejunum and ileum are rare and this segment of gastrointestinal tract is relatively inaccessible to conventional endoscopy, leading to a delay in diagnosis. Due to its rarity, data of primary jejunoileal tumors is still scarce, especially in India where diagnostic modalities like capsule endoscopy is not widely available. Herein we aim to discuss the clinico-radiologic findings, pathology and surgical management of such tumors. Methods: Of the total 51 small bowel resections done in our institute during the period from year 2012 to 2015, 14 patients were identified who were diagnosed with jejunoileal benign/malignant jejunoileal tumors. Records were analysed with respect to patient demographic data, clinical features, radiologic findings, surgical management, histopathology and postoperative outcomes. Results: Jejunoileal tumors are more common in males (77%) and first presentation was intestinal obstruction (50%) in majority of patients. A definite preoperative diagnosis based on radiologic/endoscopic means was possible in six patients (46%). Patients were operated and laparoscopic group showed superior outcomes in terms of postoperative complications. Conclusions: Jejunoileal tumors are an infrequent finding in surgical practice. In our study malignant tumors were more common in proximal small bowel. Computed tomography (CT) enterography can detect small bowel lesions with low sensitivity but allows evaluation of lymphadenopathy/distant metastasis. Laparoscopic resection allows initial staging and has the advantage of early recovery, less wound infection rates and better cosmesis.